A Strong Token Authentication And Cryptography Based Application And Data Access For Cloud Users (International Journal of Engineering and Computer Science, 2015)
Cloud computing is the latest trend in comuting by which various services, applications and other computing things can be delivered as a service. Mainly it is a formal combination of distributed, grid, cluster, elastic and utility computing. Such computation provides a quality of service based robust usage experience for the user. It serves reduced complexity and service expandability for making standardization. This leads to improved operational efficiencies and offers the client reduced predictable annual costs. Other benefits were realized in areas, such as self service, service catalog, automatic provisioning and deprovisioning, and capacity flexibility. A cloud provides clients with features, such as disaster recovery, security, and metering, which enable clients to reduce costs, increase standardization, and improve business continuity In cloud the data center is the location where the users all confidential information is stored by some security schemes provided by the service provider. Along with users normal data there is any more secure and private data which need to be hidden from even service provider and that type of control is not provided by any provider in the market. Any organization needs securing access to corporate networks, protecting the identities of users, ensuring that a user is who he claims to be and protecting the integrity of business-critical transactions. However, the recent surge in high-profile security threats, as well as evolving business environments requires entirely new considerations for access control. Cloud offerings and mobile platforms represent a shift in how trust and control is established and maintained.  This evolving environment requires a comprehensive set of security services, yet flexible enough to quickly adapt to ever changing requirements without impacting the applications and access control infrastructure in use. Smooth migration is an essential aspect of such flexibility. With this work, the aim is to make the application level of security provided by any of the servers or provide more effectively and according to the users need. For achieving the confidentiality attribute based encryption is used. Digital signature and multi factor authentication like single sign on one (SSO) are some of their examples. They should be delivered as a service so that multiple small scale companies might also integrate them to serve their users in a better way. Multiple authentication mechanisms, like digital signatures, certificates or 2-factor security and several identity validators can coexist and can be combined to suite the most complex needs.